Bentuk Desain dan Pemilihan Jenis Tanaman Lahan Pasca Tambang Nikel di Desa Tangofa Provinsi Sulawesi Tengah - Sandi, Reski; Shaddad, Aqsal Ramadhan (Jurnal of Mining Insight, 2024)
Environmental changes due to mining business are generally irregular, and most tend to be a steep relief. The objective of this research is to produce the reclamation design and to determine the right type of vegetation for planting in the former nickel mining area. This study employs qualitative research method which consist of field survey data collection, precipitation data, and size of the reclamation design as well as the history of the company being analyzed. Referring to the results of this study, the design of reclamation is vital in mine planning based on the principles as stipulated in the goverment regulation of the republic of indonesia no. 78 the year 2010. In relationt to the planned closure of the post-mining land. It is necessary to design the land after the mining activities expire considering that the land would be utilized by its allocation. Making a reclamation design used the bench method, by forming terraces since the relief was quite steep. Based on the calculation of geotechnical science by the company, the results of the slope was quite optimal with a value of SF ± 1,5 in the 3D design as reference drawings for reclamation design. Plants suitable for early revegetation is sengon, it is based on the analysis performed on 2 (two) soil chemical properties located in blok X for micro nutrient parameters. The soil pH at this location was categorized as a weak acid, and the nutrient content at the research site was classified high since it possessed higher than the averagae value based on laboratory results.